Une Bible chiriguano - Isabelle Combès (Caravelle)
There is just one book about the Kurujuki battle between the Chiriguano Indians and the Republican Army in 1892, in the Bolivian Chaco. Hernando Sanabria Fernández, the author, recreated Biblical history by tracing the Chiriguano tumpa on the Christ figure. This imagery is still repeated by historians and several social actors, and lies at the base of current representations of the battle. The book by Sanabria Fernández thus became the Bible that his author aspired to rewrite.